Considerations about the relation between occlusal trauma and periodontal/peri-implant disease - Junqueira, Rafael Binato; Saavedra, Guilherme de Siqueira F. Anzaloni; de Macedo, Nelson Luiz (Brazilian Dental Science, 2015)
The occlusal trauma is an injury to the insertion apparatus as a result of excessive occlusal force, and its interaction with periodontal/peri-implant disease remains controversial topic in the literature. The aim of this study was to review the literature about the relationship between occlusal trauma and periodontal/peri-implant disease, through an analysis of experimental studies in humans and animals, as well as systematic reviews that discussed the role of occlusal factor as etiological or aggravating periodontal/peri-implant disease. It was concluded that, although not considered a cause for the development of periodontitis and peri-implantitis, occlusal trauma can exacerbate bone loss around the teeth or implants. Moreover, the diversity of methodologies in studies on the subject might contribute to the conflicting results available, highlighting the importance of standardization and more detailed research criteria. Keywords: Dental implants; Periodontal diseases; Peri-implantitis; Traumatic dental